UPAYA GURU DALAM MENGATASI KESULITAN MEMBACA PERMULAAN PADA SISWA KELAS II DI SDN 3 REMPEK TAHUN AJARAN 2023/2024 - Roni, Pita; Rahayu, Fitriani; Marzoan, Lalu (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research aims to determine the factors that cause initial reading difficulties in class II students at SDN 3 Rempek and teachers' efforts to overcome initial reading difficulties in class II students at SDN 3 Rempek in the 2023/2024 academic year. This type of research uses a descriptive qualitative type with a case study approach. The data sources in this research were obtained through the process of interviews, observation and documentation. Data analysis techniques are: data condensation, data presentation, and data verification. The conclusion of this study found that the factors causing students' learning difficulties occurred due to two factors, namely: internal factors and external factors. The internal factors of the students themselves are intellectual and psychological factors, while external factors include the family environment, school environment and teacher factors. Efforts made by teachers to overcome difficulties in learning to read at the beginning of grade II students are: (1) diagnosing students' difficulties, (2) applying the alphabet method and syllable method, (3) reading 10 minutes before starting learning and before going home, (4) collaborate with students' parents, (5) Provide additional hours, and (6) Provide reading materials.